Levels of self-efficacy and adjustment among Filipino elementary teachers in the re-opening of face-to-face classes - Carl O. Dellomos; Mae Angela D. Dela Cruz; Shirlex Martinez; Klint Niño L. Miciano; Reinna Jhozea C. Tiongson; Jhasper M. Ty; Marie Grace Pamela G. Faylona; John Mark M. Tumaob; Sheila G. Tan; Benjamin M. Castro (International Research Journal of Science, Technology, Education, and Management)
The learning community has been profoundly affected by the COVID-19 pandemic. In the Philippines, Filipino teachers faced challenges such as adjustment to new pedagogical concepts, styles of delivery, and different environments due to the limitations imposed by the nationwide lockdown. The Department of Education (DepEd) shifted promptly to switch to online learning and develop the Basic Education Learning Continuity Plan (BE-LCP). This plan outlines how education will continue during the pandemic, with a primary focus on protecting the well-being and safety of students, instructors, and staff. Furthermore, the Department of Education mandated the return of five days of in-person classes two years later, when education had recovered to normal, following the effects of COVID-19. The aim of this study is to describe the levels of teachers’ self-efficacy, adjustment, and the relationship between these variables when the reopening to five-day face-to-face classes was implemented. The respondents of the study were teachers from Beata Elementary School at Pandacan, Manila. A correlational method was used to perform the research. The researchers utilized a survey questionnaire that included the Teachers' Sense of Efficacy Scale (TSES), created by Megan Tschannen-Moran and Anita Woolfolk Hoy in 2001, as well as the Teachers' Adjustment Scale developed by the researchers. Data revealed that there is a high level of self-efficacy (x̄=8.04) and adjustment (x=8.38) among the Filipino elementary teachers. The study revealed a positive correlation between self-efficacy and teacher adjustment, indicating that the higher the level of self-efficacy, the higher the level of teacher adjustment.